DuoStim: a new option for fertility preservation for a woman with Turner syndrome. (1st December 2020) - Ito, Ayumu; Katagiri, Yukiko; Tamaki, Yuko; Fukuda, Yusuke; Oji, Ayako; Morita, Mineto
Abstract: Introduction: Turner syndrome (TS) is associated with hypergonadotropic hypogonadism due to gonadal dysgenesis, which results in premature ovarian failure and subsequent infertility. Therefore, counseling and evaluation for fertility preservation are required as early as possible for women with TS. Case presentation: A 23-year-old unmarried woman with mosaic TS (45, X [4/30] 46, XX [26/30]) presented to the pediatric department of our hospital for fertility counseling; she was accompanied by her mother. She was referred to the reproduction center of our hospital for ovarian reserve assessment and counseling regarding fertility preservation. We decided to retrieve oocytes using DuoStim as the controlled ovarian stimulation protocol. During the first and second oocyte retrievals, a total of 17 (9 and 8, respectively) mature metaphase II oocytes were cryopreserved. Conclusion: DuoStim may be a useful option for fertility preservation for women with TS and reduced ovarian reserve. This new strategy may obtain the required number of oocytes in the shortest time and preserve the future fertility of women with TS.